Rancang Bangun Sistem Informasi Penerimaan Mahasiswa Baru (SPMB) Berbasis Web pada Universitas Sanad (UNISAN) - Fiki Maipron; Muhammad Yunus Rangkuti; Muhammad Fadhiil Agam; Riky Cahya Juniar (Jurnal Riset Informatika dan Inovasi, 2026)
The development of information technology requires educational institutions to improve service efficiency, including in the new student admission process. This study aims to design and implement a web- based New Student Admission Selection (SPMB) information system at Sanad University (UNISAN) using the Waterfall method. The system is designed to overcome the problems of manual registration which is time- consuming and risks data loss. The application integrates key features such as prospective student account registration, biodata completion, document uploading, and graduation verification by admins. Development was carried out using the Native PHP programming language and MySQL database. The implementation results show that this application is able to facilitate prospective students in registering online and assist the PMB committee in managing applicant data centrally and efficiently.